Investigation of factors associated with delayed initiation of breastfeeding in Papua New Guinea: a cross-sectional study - Lisa M Vallely; Francis Pulsan; McKenzie Maviso (BMJ Paediatrics Open)
Background Breastfeeding within the first hour of birth is critical for newborn survival. However, in Papua New Guinea (PNG), about 40% of newborns are not breastfed within the first hour of birth. This study aimed to determine the prevalence and factors associated with delayed initiation of breastfeeding in PNG.Methods This study used secondary data from the 2016–2018 PNG Demographic and Health Survey, a nationally representative cross-sectional study. A total weighted sample of 4748 women aged 15–49 were included. Complex samples analysis was performed to determine the direction of association between the independent variables and delayed initiation of breastfeeding.Results About a quarter (24.6%) of women delayed initiation of breastfeeding. Women with an unplanned pregnancy (adjusted OR (AOR) 1.32; 95% CI 1.03 to 1.68), those who had a caesarean section (AOR 3.16; 95% CI 1.39 to 7.17), those who did not initiate newborn skin-to-skin contact immediately after birth (AOR 1.83; 95% CI 1.41 to 2.38) and those who watched television (AOR 1.39; 95% CI 1.11 to 1.75), and were from the Momase region (AOR 1.31; 95% CI 1.00 to 1.93) had higher odds of delayed breastfeeding initiation. Conversely, the odds of delayed initiation of breastfeeding was lower among women who read a newspaper or magazine (AOR 0.76; 95% CI 0.61 to 0.95), were from the Southern (AOR 0.81; 95% CI 0.56 to 1.15) and Highlands (AOR 0.86; 95% CI 0.58 to 1.29) regions, and gave birth at home or in the village (AOR 0.69; 95% CI 0.49 to 0.96).Conclusion One in four women in this study delayed initiation of breastfeeding until after 1 hour after birth. Interventions to promote optimal breastfeeding require a multi-sectoral approach, as well as bolstering health workers’ capacity to encourage and support early initiation of breastfeeding during the antenatal and early postnatal periods.